EFFECT OF VARIETY AND POULTRY MANURE ON THE GROWTH OF PAWPAW (Carica Papaya) SEEDLINGS - Babagana, B. M*.; Dawaki, J. A.; Fagam, A. S.; Shuaibu, Y. M.; Yusuf., Z. A. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
A field experiment to determine the effect of variety and poultry manure on the growth of pawpaw seedlings was conducted during 2023 and 2024 dry seasons at Tafawa Balewa Road, Federal Low-cost Housing Estate Bauchi, Bauchi State, Nigeria. The treatments consisted of five Poultry manure levels (0.0kg, 0.2kg, 0.4kg, 0.6kg and 0.8kg/pot) and two varieties of papaya (Calina IPB9 True Dwarf and Sun Grads) which were factorially combined and arranged in a randomized complete block design (RCBD) with three replications. The results revealed that the treatments significantly (P≤0.05) affected plant height with poultry manure rate of 0.8kg/pot given the tallest plants throughout the study period. The result further showed a significant (P≤0.05) effect of the treatments on number of leaves where poultry manure rate of 0.8kg/pot proved to be better than the other rates used. A significant effect (P≤0.05) was recorded on stem girth and number of nodes with poultry manure rate of 0.8kg/pot taken the lead throughout the study period. Furthermore, there was a significant (P≤0.05) effect in moisture stress where poultry manure level of 0.2kg/pot showed higher remaining leaves (RML) and higher dry weight than the other treatments considered. Variety on the other hand, except on plant height in 2023 where sun grads proved to be statistically (P≤0.05) better, no significant (P≤0.05) difference was observed throughout the study period. The application of cured poultry manure enhanced growth performance and resistance to moisture stress of the considered papaya seedlings. Based on the result of this findings, application of poultry manure to growing pawpaw seedlings at the rate of 0.8 kg/pot is recommended in the study area. Trials with other organic manure as a source of nutrients are therefore recommended.